Pretest Score for Predicting Microbubble Contrast Agent Use in Stress Echocardiography: A Method to Increase Efficiency in the Echo Laboratory - Mathieu Bernier; Sahar S. Abdelmoneim; Stuart Moir; Robert B. McCully; Patricia A. Pellikka; Sharon L. Mulvagh (Cardiology Research and Practice)
Background. In stress echocardiography, contrast agents are used selectively to improve endocardial border definition. Early identification of candidates may facilitate use of these agents in small and medium volume laboratories where resources are limited. Methods. We studied 15232 patients who underwent stress echocardiography. Contrast agent was used if 2 or more ventricular segments were not adequately visualized without contrast. Logistic regression models were used to evaluate the association between individual characteristics and contrast use. An 11-point score was derived from the significant characteristics. Results. Variables associated with microbubble use were age, sex, smoking, presence of multiple risk factors, bodymass index (BMI), referral for dobutamine stress echocardiography, history of coronary artery disease, and abnormal baseline electrocardiogram. All variables except BMI were given a score of 1 if present and 0 if absent; BMI was given a score of 0 to 4 according to its value. An increased score was directly proportional to increased likelihood of contrast use. The score cutoff value to optimize sensitivity and specificity was 5. Conclusions. A pretest score can be computed from information available before imaging. It may facilitate contrast agent use through early identification of patients who are likely to benefit from improved endocardial border definition.